Determination of the Chemical Composition and Antioxidant Activity of Artemisia vulgaris and Artemisia absinthium Growing in the Conditions of the Semey Region - Kabdulkarimova, Kulbanu K.; Dinzhumanova, Raushan; Olzhayeva, Rauza; Karimova, Aikunim A.; Uzbekova, Saltanat Ye.; Orazalina, Ainash; Dosbayeva, Altynai; Lauyenova, Saniya A. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The action of the main biologically active substances contained in medicinal products becomes obvious in combination with the action of macro- and micro-elements that determine the natural mineral composition of the plant. AIM: The objective of this study was comparative study of the composition of macro- and micro-elements of two representatives of the genus Artemísia L. on the example of Artemisia vulgaris and Artemisia absinthium and their antioxidant activity. METHODS: In this work, the following stages of the study were used: Gathering and preparation of medicinal plant (MP) materials; method of sampling the test material for analysis; determination of humidity; and determination of the quantitative composition by inductively coupled plasma mass spectrometry (ICP-MS) and atomic emission spectrometry ICP (AES-ICP). Determination of antioxidant activity was carried out by photometry. The accuracy of the analysis results was checked by the method of standard additives. Each sample was accurately analyzed in accordance with the recording of the instrument methodology. The necessary operating modes of the mass spectrometer were set in accordance with the manufacturer’s recommendations. To verify the reliability (accuracy) of the analysis results of micro- and macro-elements of MP, the determination was carried out by two methods: ICP-MS with ICP and AES-ICP. RESULTS: It has been established that the indicators of the investigated MP do not exceed the permissible values for the content of residual moisture and ash. The presence of macro- and micro-elements in both objects of the study is also shown. Quercetin was identified in A. absinthium and A. vulgaris. CONCLUSION: The obtained results of qualitative and quantitative indicators of the content of macro- and micro-elements, such as potassium, calcium, sodium, magnesium, copper, iron, manganese, as well as an analysis of the antioxidant activity of samples of A. absinthium and A. vulgaris, allow us to conclude that the studied plants are promising as a component composition for creating preparations based on them.